Constitutionalism at the Nexus of Life and Law. (November 2020) - Hurlbut, J. Benjamin; Jasanoff, Sheila; Saha, Krishanu
This essay introduces a collection of articles gathered under the theme of "law, science, and constitutions of life." Together, they explore how revolutions in notions of what biological life is are eliciting correspondingly revolutionary imaginations of how life should be governed. The central theoretical contribution of the collection is to further elaborate the concept of bioconstitutionalism, which draws attention to especially consequential forms of coproduction at the law–life nexus. This introduction offers a theoretical discussion of bioconstitutionalism. It explores the constitutional significance of interplay between scientific and technological power over life and a given political community's shared imaginary of what modes of reasoning, judgment, and rule are proper and legitimate in a well-ordered state. It argues that knowing what life is for purposes of governance does not follow from scientific knowledge alone. Rather, such knowledge is refracted through culturally distinctive imaginaries that commit societies to particular understandings of what life means and what should be done to encourage its flourishing.